2022
DOI: 10.1016/j.jds.2021.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2,3,5,4′-tetrahydroxystilbene-2-O-b-D-glucoside-induced proliferation and differentiation of dental pulp stem cells in 2D and 3D culture systems—gene analysis

Abstract: Background/purpose Culture environments play a critical role in stem cell expansion. This study aimed to evaluate the effects of 2,3,5,4′-tetrahydroxystilbene-2-O-b-D-glucoside (THSG) on the proliferation and differentiation of human dental pulp stem cells (DPSCs) in 2-dimensional (2D) and 3-dimensional (3D) culture systems. Materials and methods Human DPSCs were seeded in T25 flasks for 2D cultivation. For the 3D culture system, DPSCs were mixed with microcarriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…According to the research by Bu et al, DPSCs cultured in microsphere-forming plates had higher levels of differential gene expression in regeneration-related gene categories and had a stronger capacity for multipotent differentiation than DPSCs cultured in conventional monolayer plates ( Bu et al, 2020 ). Wu et al (2022) found that 2,3,5,40-tetrahydroxystilbene-2-O-D-glucoside may improve DPSCs stemness when used in a rotating bioreactor. Additionally, the expression of oncogenes and apoptotic genes in DPSCs was markedly decreased.…”
Section: Expansion In Large Scalementioning
confidence: 95%
“…According to the research by Bu et al, DPSCs cultured in microsphere-forming plates had higher levels of differential gene expression in regeneration-related gene categories and had a stronger capacity for multipotent differentiation than DPSCs cultured in conventional monolayer plates ( Bu et al, 2020 ). Wu et al (2022) found that 2,3,5,40-tetrahydroxystilbene-2-O-D-glucoside may improve DPSCs stemness when used in a rotating bioreactor. Additionally, the expression of oncogenes and apoptotic genes in DPSCs was markedly decreased.…”
Section: Expansion In Large Scalementioning
confidence: 95%